Carrying Capacity of Tepian Batu Lake in Teratak Buluh Village Siak Hulu District Kampar Regency Riau Province Based on Total-P - Theresia Tifany Saragih; Tengku Dahril; Asmika Harnalin Simarmata (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractCarrying capacity is defined as the ability of aquatic environment to support the life of organisms in that area. A research aims to determine the carrying capacity and the number of floating net cages which can be operated in Tepian Batu Lake based on total phosphorus concentrations. The research was conducted from June to July 2019. Sampling was determined at 3 locations, namely Station 1 (inlet area), Station 2 (KJA area) and Station 3 (outlet area). Each Station has                 2 sampling points, namely surface and in 2 Secchi depth. Sampling was carried out 3 times once/week. Water quality parameters measured were total phosphorus, depth, transparency, temperature, pH, dissolved oxygen and biochemical oxygen demand. The carrying capacity based on Total-P was analyzed by Beveridge formula (2004). The results showed that Total-P concentration 0.071-0.174 mg/L. Water quality parameters were as follows : depth 354-395.5 cm, transparency 57-63.3 cm, temperature 28.67-30.33oC, pH 5-5.67, DO 3.34-5.18 and BOD5 3.03-8.25 mg/L. The carrying capacity of Tepian Batu Lake was 1.1607 ton/year or the number of floating net cages 4 units. Based on carrying capacity of Tepian Batu Lake, it can be concluded the current number of floating net cages (FNC) has exceeded the reservoir’s carrying capacity. Keywords : Beveridge, Water quality, Biochemical oxygen demand, Dissolved                       oxygen, Floating net cages